Przerwa w karze w świetle orzecznictwa Sądu Najwyższego i sądów apelacyjnych : przegląd judykatów za lata 2020–2021 - Mrozek, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The work is devoted to the analysis of the judicial decisions made by the Supreme Court and selected courts of appeal in the scope concerning the institution of interrupting the execution of the imprisonment sentence. The author was interested only in the most recent judicates issued in 2020–2021. In order to improve the readability of the text, the analysis of a specific decision begins with quoting its thesis, which is then accompanied by a short commentary. The discussed provisions focus on the most important problems which arise in connection with the practical use of the interruption of penalty.
Keywords: interruption of penalty; personal reasons; mental illness; total penalty; imprisonment